2021
DOI: 10.1039/d1dt00612f
|View full text |Cite
|
Sign up to set email alerts
|

Proton conductivity as a function of the metal center in porphyrinylphosphonate-based MOFs

Abstract: The rational design of metal-organic frameworks (MOFs) is highly important for the development of new proton conductors. Porphyrinylphosphonate-based MOFs, providing the directed tuning of physical and chemical properties of materials...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…The high surface area, crystallinity, controllable pore size, exibility, and functionalization of the porous surface are some of the main characteristics which determine the versatility of MOFs. 1 Hence, MOFs are investigated in applications such as gas storage and separation, 2-6 catalysis, [7][8][9] drug delivery, [10][11][12] proton conductivity, [13][14][15] magnetism [16][17][18][19] etc. 20 In our research for discovering novel original porous frameworks with multifunctional linkers, we mainly focused on porphyrinic building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…The high surface area, crystallinity, controllable pore size, exibility, and functionalization of the porous surface are some of the main characteristics which determine the versatility of MOFs. 1 Hence, MOFs are investigated in applications such as gas storage and separation, 2-6 catalysis, [7][8][9] drug delivery, [10][11][12] proton conductivity, [13][14][15] magnetism [16][17][18][19] etc. 20 In our research for discovering novel original porous frameworks with multifunctional linkers, we mainly focused on porphyrinic building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…The second step corresponds to the loss process of guest DMA molecules at 82.6–156.8 °C in channels of CUST-736 . 17 Upon further heating over 390 °C, the decomposition of the framework is observed (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…59 Recently, we have demonstrated the perspectives for the application of porphyrinylphosphonates as an organic moiety of metal-organic frameworks, demonstrating a high efficiency as proton conductors with tunable physical-chemical properties. [64][65][66] In parallel, two hydrogen-bonded frameworks based on nickel(II) 5,10,15,20-tetrakis(4-phosphonatophenyl) porphyrinate have been obtained. 67 It was found that the number of hydrogen bonds and types of binding phosphonate groups of porphyrin depend on the presence of lattice water molecules in the structure that may affect the proton-conducting properties of these materials.…”
Section: Introductionmentioning
confidence: 99%